Piekielne laboratorium, niepodległy duch. Wizja Islandii w relacjach z podróży Samuela Kneelanda i BayardaTaylora - Jakubczyk, Radosław (2022)
In the second half of the nineteenth century, Iceland had become quite a popular destination for American travelers. Among this group were Samuel Kneeland, a physician and naturalist, and Bayard Taylor, a poet, translator and reporter for the New York Tribune, who came to Iceland in the summer of 1874 to attend the millennial celebration of the first settlement of that island. They visited Þingvellir, a site that many Icelanders considered and still consider “holy ground”, the Haukadalur valley, or the valley of geysers, and Reykjavík, the main and at the time the only Icelandic city. Two travelogues, entitled Egypt and Iceland in the Year 1874 and An American in Iceland, published in 1874 and 1876, respectively, were the fruit of their visit to Iceland. The present paper offers a reading of these accounts in order to trace the strategies employed by American authors to describe nineteenth-century Iceland and Icelanders.
Keywords: Kneeland, Samuel; Taylor, Bayard